2019
DOI: 10.3390/en12234461
|View full text |Cite
|
Sign up to set email alerts
|

Interdependence Between Renewable-Energy and Low-Carbon Stock Prices

Abstract: In the transition to a low-carbon economy, climate-resilient investors may be inclined to buy renewable-energy or other low-carbon assets. As the diversification benefits of investment positions in those assets depend on interdependence between their market prices, we explore that interdependence in the European and USA stock markets. We model the dependence structure using bivariate copula functions and evaluate price spillovers between those markets using a conditional quantile dependence approach that accou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…The few studies that considered carbon price documented varying results with Kumar et al (2012) and Dutta et al (2018) establishing absence of a significant influence of carbon price on CERs. However, Hanif et al (2021), Reboredo et al (2019) and Wang and Cai (2018) established a significant positive effect of carbon price on CERs.…”
Section: Energy Security Elements and Clean Energy Stock Returns/vola...mentioning
confidence: 91%
“…The few studies that considered carbon price documented varying results with Kumar et al (2012) and Dutta et al (2018) establishing absence of a significant influence of carbon price on CERs. However, Hanif et al (2021), Reboredo et al (2019) and Wang and Cai (2018) established a significant positive effect of carbon price on CERs.…”
Section: Energy Security Elements and Clean Energy Stock Returns/vola...mentioning
confidence: 91%
“…Furthermore, Reboredo et al. (2017, 2019) pointed out a significant correlation between the price of oil and the stock prices, including clean energy, renewable energy and low-carbon industries. For the green bond market, Pham (2016) explored the influence of the traditional bond market on the fluctuation of the green bond market and revealed that the overall influence of the traditional bond market tended to spread to the green bond market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For example, for the green stock market, Reboredo (2015) and Dutta (2017) found that the fluctuation of crude oil prices would increase the systemic risk of renewable energy companies' stock prices. Furthermore, Reboredo et al (2017Reboredo et al ( , 2019 pointed out a significant correlation between the price of oil and the stock prices, including clean energy, renewable energy and low-carbon industries. For the green bond market, Pham (2016) explored the influence of the traditional bond market on the fluctuation of the green bond market and revealed that the overall influence of the traditional bond market tended to spread to the green bond market.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The work in [3] presents a high-level overview of the integration of RES into the electric power system in Croatia, focusing on grid connections, power balancing, inertia reduction aspects and market participation. The market impact of RES is also debated in [4], where the case of wind plants coupled with pumped hydro energy storage is examined using various optimization algorithms, and in [5], dealing with the interdependence between renewable energy and low-carbon stock prices. The study in [6] discusses the impact of RES on power system flexibility, and, similarly, the study in [7] contains a techno-economic analysis of the application of energy storage systems on wind farms to provide short-term ancillary services such as inertia response and frequency support.…”
Section: Introductionmentioning
confidence: 99%